A revised chronology for the archaeology of the lower Yangtze, China, based on Bayesian statistical modelling. (November 2015) - Long, Tengwen; Taylor, David
Abstract: Bayesian statistical modelling, based on 128 existing radiometric (radiocarbon and thermoluminescence) dates and associated information from a database totalling 252 dates, was used to generate a revised chronological framework for the lower Yangtze, eastern China. The framework covers the period from the terminal Pleistocene through to the mid to late Holocene, and thus the appearance of and subsequent developments in food production in the region, which is marked in the archaeological record by seven cultural phases. Results indicate that the age span of the Shangshan, Kuahuqiao, Hemudu, Majiabang, Songze, Liangzhu, and Maqiao cultural phase were, respectively, ca. 10, 800–8600 cal BP, ca. 7900–7200 cal BP, ca. 7100–5200 cal BP, ca. 7200–5200 cal BP, ca. 5700–5200 cal BP, ca. 5500–4000 cal BP, and ca. 3700–3200 cal BP. In addition to providing a basis for a more robust absolute dating of archaeological remains in the lower Yangtze in the future, the results raise important questions deserving of further research. These questions relate to a priori assumptions concerning the degree of temporal separation of Neolithic cultural phases on the Yangtze Delta. A coexistence of cultures on the Yangtze Delta evident in the results does not accord with the existing model for the region, which generally assumes a replacement of one cultural phase by the next. Coexistence of cultures could have been supported by a high degree of environmental variability on the Yangtze Delta, or by social factors, such as different levels of preference towards innovations or traditions, or some combination of factors. Highlights: We establish a Bayesian chronological model for the lower Yangtze. We discuss possible overlaps among different cultural phases of the lower Yangtze. We urge emphasis on chronological controls in lower Yangtze studies.